OPTIMALISASI ORIENTASI DAN PENEMPATAN KARYAWAN DALAM MENINGKATKAN PRODUKTIVITAS: STUDI KASUS PADA AYAM SWASTA CIREBON - Harmen, Hilma; Sinaga, Yohana Br; Ikhwan, Al; Arifa, Nazwa; Natalia, Robema; Kristianus, Julius (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This article will discuss optimizing the employee orientation and placement system to increase productivity at Cirebon Private Chicken. The two-month orientation program aims to accelerate the adaptation of new employees and enhance their understanding of the company culture and job responsibilities. The main problem found was the lack of regular evaluation of the program's effectiveness, making it difficult to identify aspects that needed improvement. In addition, the mismatch of employees' skills with their assigned positions led to inefficiency and decreased productivity. The results showed that regular evaluation is necessary to ensure the effectiveness of onboarding and to adapt the program to the diverse experience levels of employees. Competency-based selection can also improve the match between skills and job positions, ensuring that employees are placed in roles that align with their strengths and expertise. Furthermore, the utilization of technology in HR management, such as digital systems for performance monitoring and e-learning in onboarding, can enhance efficiency and engagement. The integration of gamification in training programs can further motivate employees, leading to higher commitment and productivity. Using a qualitative approach, this article explores issues in employee onboarding and placement and provides ways to optimize competency-based strategies and technology to make a work environment more productive and positive.